Effect of MSCs on Vascular Endothelial Growth Factor (VEGF), C-Reactive Protein (CRP), Tumor Necrosis Factor-Alpha(TNF-α;), Triglyceride, Pancreatic Beta Cells And Insulin Resistance in Obese Type 2 Diabetic Rat Model - Vito Mahendra Eka Saputra; Agung Putra; Titiek Sumarawati; Sugeng Ibrahim; Meidona Nurul Mila; Arini Dewi Antari; Fadhli Rizal Makarim; Iffan Alif; Ghaitsa Hasnadia Anggoro; Namira Sa'adah Latifah; Rania Maharani; Windy Listiana (Medicinski glasnik, 2025)
Aim: to investigate the potential of SG followed by injection of MSCs in type 2 diabetic rats with obesity in improving IR. Methods: This study used a pre and post-control group design with 24 rats divided into three groups: Control (C), SG, and SG + MSCs (SG+M). On day 10, the level of vascular endothelial growth factor (VEGF), tumor necrosis factor-alpha (TNF-?), C-reactive protein (CRP), triglyceride (TG), pancreatic beta cells, and homeostasis model assessment of IR (HOMA-IR) was evaluated using qRT-PCR, ELISA, and immunohistochemistry. Results: A significant decrease of TNF-? (1.179 pg/mL), CRP(209 pg/mL), and TG levels (82,83 15,02pg/mL) in all treatment groups on day 10, in which SG + M group showed optimum inhibition was found (p < 0.05). This result was in line with the optimum increase of VEGF (8,1500 ± 2,47397) and pancreatic beta cell(10,1783±0,47) in SG + M group (p < 0.05). Moreover, our study also revealed the optimum decrease of HOMA-IR in SG+M group on day 10 (49,8233 ± 1,07303). Conclusion: A combination of SG and MSCs can optimally improve insulin resistance by inhibiting TNF-?, CRP, and TG level and upregulating VEGF and pancreatic beta cell in an obese T2DM rat model
Keywords: adipose tissue; Bariatric Surgery; cytokines; Progenitor Cells; Sleeve Gastrectomy